Analisis Faktor-faktor yang Mempengaruhi Indeks Pembangunan Manusia Kabupaten Malang Berbasis Pendekatan Perwilayahan dan Regresi Panel - Zulfikar Mohamad Yamin Latuconsina (P4W LPPM IPB, 2017)
Regionalization approach is a kind of approach to manage and to achieve the development goals based on the characteristics of a region. The development system of Malang Regency is conducted through regionalization approach which divided the area into six Development Areas (WP). Furthermore, the typology of development area in Malang Regency can be divided into three typology (urban, peri-urban and rural). This research aims to analyze factors that influence the human development index (HDI) of Malang Regency based on regionalization approach and panel regression. Data panel regression method was used in analyzing the data. The results of the research showed variables that have a positive and significant influence to the human development index in each typology of development areas of Malang Regency consisting of the number of health facilities, the number of nurse-midwife and the population density in typology I (urban); the ratio of school per students at primary school and the population density in typology II (peri-urban); and the number of nurse-midwife in typology III (rural).